A New Strategy for Europe - Karl Aiginger; Margit Schratzenstaller (Intereconomics, 2016)
WWWforEurope has developed a comprehensive strategy to set Europe on a path to a socio-ecological transition. The strategy begins by renouncing the long-established concept of using GDP growth figures as the benchmark for economic and societal progress. In contrast, it sets “well-being in a sustainable environment” as the optimal benchmark for economic performance and social progress.
Keywords: 330; Politischer Wandel; Sozialer Wandel; Wachstumspolitik; Wirtschaftswachstum; EU-Staaten